Coronavirus infections: health care planning based on Orem's Nursing Theory - Tayomara Ferreira Nascimento; Graziela Maria Ferraz de Almeida; Marielle Poyo Bello; Rosemary Pereira Lino da Silva; Cassiana Mendes Bertoncello Fontes (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to report the experience of professors and students of a graduate course on nursing care in coping with the new coronavirus (COVID-19) based on Self-Care Theory. Method: the active methodologies used were a literature search and seminar presentations, with an understanding of Orem's theoretical concepts: health; man; self-care; universal, developmental and health deviation requirements; self-care activities; self-care deficits; the required therapeutic demand; nursing systems. The pandemic was considered a health deviation that requires critical thinking and nursing care planning. Methodological frameworks to classify nursing diagnoses, interventions, and outcomes were used. Results: for each health deviation, nursing systems were identified; self-care deficits, diagnoses; actions, interventions; and the form of assessment, outcomes. Final considerations: theoretical-practical reflections of the academic context support nursing care planning.